2023
DOI: 10.3390/cells12010191
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of GBA Deficiency in the Autophagy–Lysosome System in Parkinson’s Disease Associated with GBA

Abstract: GBA gene variants were the first genetic risk factor for Parkinson’s disease. GBA encodes the lysosomal enzyme glucocerebrosidase (GBA), which is involved in sphingolipid metabolism. GBA exhibits a complex physiological function that includes not only the degradation of its substrate glucosylceramide but also the metabolism of other sphingolipids and additional lipids such as cholesterol, particularly when glucocerebrosidase activity is deficient. In the context of Parkinson’s disease associated with GBA, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 187 publications
0
9
0
Order By: Relevance
“…In GBA1-related PD, impaired lysosomal clearance of autophagic substrates and aggregate-prone proteins is linked to decreased GBA activity and the buildup of α-syn species. 32 S-nitrosylation of the autophagic adaptor protein p62 inhibits autophagic flux, leading to the intracellular accumulation of misfolded proteins. This accumulation may contribute to the spread of aggregated α-syn in PD and LB dementia.…”
Section: Autophagy In Parkin Son ' S Dise a Sementioning
confidence: 99%
See 1 more Smart Citation
“…In GBA1-related PD, impaired lysosomal clearance of autophagic substrates and aggregate-prone proteins is linked to decreased GBA activity and the buildup of α-syn species. 32 S-nitrosylation of the autophagic adaptor protein p62 inhibits autophagic flux, leading to the intracellular accumulation of misfolded proteins. This accumulation may contribute to the spread of aggregated α-syn in PD and LB dementia.…”
Section: Autophagy In Parkin Son ' S Dise a Sementioning
confidence: 99%
“…Variants in the GBA gene, which encodes the lysosomal enzyme glucocerebrosidase (GBA), have been associated with a malfunctioning autophagy‐lysosome system and a subsequent reduction in autophagy‐mediated turnover of α‐syn, representing significant risk factors in PD development. In GBA1‐related PD, impaired lysosomal clearance of autophagic substrates and aggregate‐prone proteins is linked to decreased GBA activity and the buildup of α‐syn species 32 . S‐nitrosylation of the autophagic adaptor protein p62 inhibits autophagic flux, leading to the intracellular accumulation of misfolded proteins.…”
Section: Autophagy In Parkinson's Diseasementioning
confidence: 99%
“…GBA encodes the lysosomal enzyme glucocerebrosidase, which is involved in the breakdown of glucosylceramide. Reduced glucocerebrosidase activity is associated with impaired lysosomal function and α-synuclein accumulation ( Pang et al, 2022 ; Pradas and Martinez-Vicente, 2023 ).…”
Section: The Autophagy Lysosome Pathway In Pdmentioning
confidence: 99%
“…Many genes and genetic loci are now linked to the risk for PD using modern genetic methods. Many studies suggest that ALP might be involved in sporadic PD ( Orenstein et al, 2013 ; Zavodszky et al, 2014 ; Ysselstein et al, 2019 ; Cui et al, 2021 ; Pang et al, 2022 ; Shrivastava et al, 2022 ; Pradas and Martinez-Vicente, 2023 ). A recent meta-analysis of genome-wide association studies (GWAS), interrogating data from >13,000 PD patients and > 95,000 controls, identified 26 genetic loci across the genome associated with PD.…”
Section: The Autophagy Lysosome Pathway In Pdmentioning
confidence: 99%
See 1 more Smart Citation